Effect of Mineral Mix Supplementation in Silage of Palm Frond Grated (PFG) and Palm Sludge on Digestibility and Delay Quality By In Vitro Methods - Fariani, Armina; Warly, Lili; Pratama, A. N. T.; Muslim, G. (Universitas Bengkulu, 2023)
By-products from oil palm can feed ruminants such as palm fronds (OPF) and palm oil sludge (PS). Judging from its continuous, cheap, and abundant availability from the palm oil industry, as well as a source of fiber or a component in complete feed for ruminants, it is the potential that can be used as animal feed. However, the use of oil palm fronds in livestock production is minimal due to their complex fiber structure, high lignin content, and low protein content. So, it needs management technology on OPF. The design used was a Completely Randomized Design (CRD) with three treatments and five repetitions: P0 Palm frond silage (30%) + palm sludge (70%) P1 Silage of palm fronds (30%) + palm sludge (70%) + Mineral Mix 1% P2Palm frond silage (30%) + palm sludge (70%) + Mineral Mix 2%. The data obtained were analyzed for variance according to the design used, and if there were differences between the treatments, continued analysis using the Duncan Multi Range Test Based on the results of statistical analysis showed that the silage treatment of palm frond powder and palm sludge supplemented with a mineral mix in vitro decreased the digestibility value of dry matter (P<0.05). However, different results were shown in the digestibility of organic matter, where increased digestibility occurred in treatment with supplementation of mineral mixes. The statistical analysis showed that the silage treatment of palm frond powder and palm sludge supplemented with the mineral mix in vitro showed no significant difference between treatments (P>0.05) on VFA and NH3 values. Based on the study's results, it can be concluded that mineral mix supplementation in the silage of palm frond powder and palm sludge significantly decreases the digestibility of dry matter but increases the digestibility value of organic matter. Nevertheless, the treatment given did not have a significant effect on the quality of the fermentation, which included VFA and NH3.